Corporate Governance Country Assessment : Jordan - World Bank (Washington, DC, 2013)
This report provides an assessment of Jordan's corporate governance policy framework, enforcement and compliance practices. Strengths and weaknesses are highlighted and policy recommendations are made where appropriate. Much progress was made in the regulatory environment in the 1990s, since the creation of the Jordan Securities Commission, the Amman Stock Exchange, and the Securities Depository Center. The report identifies several key next steps that focus on implementation, including: (i) developing a Code of Corporate Governance that focuses on the role, duties, and functions of the board; (ii) focused enforcement of the disclosure provisions, with continued emphasis on a review of content; (iii) revision of the Company Law to bring the policy framework into greater compliance with the OECD Principles, and (iv) a review of the regulatory jurisdictions of the three main regulatory bodies that oversee corporate governance. Together, these measures will bring Jordan into the mainstream of the worldwide corporate governance reform movement and provide new opportunities for issuers to implement international good practice.